A spouse and a house are all we need? Housing demand, labor supply and divorce over the lifecycle - Bram de Rock; Mariia Kovaleva; Tom Potoms (Institute for Fiscal Studies (IFS), 2023)
To analyze the impact of changes in the value of marriage on household decisions, we present a limited commitment framework of household behavior in which decisions are made regarding labor supply, divorce and housing demand over the lifecycle. We identify and estimate our structural model using exogenous variation in female labor supply and divorce rates due to the White v. White case in England. We conclude that limited commitment dampens the added worker effect, while the changes in the value of marriage due to a housing price shock have an asymmetric impact on individual welfare both across gender and marital state. We also show that tightening the credit market in different ways can lead to opposite behavior in terms of household savings and female labor supply.
Keywords: D14; D15; J12; J22; K36; R21; 330; Limited commitment; divorce legislation; value of marriage; housing demand; labor supply; credit market policy